Neuropsychological Aspects of a Patient With Intracranial Rosai‐Dorfman Disease: Case Report - Carolina Veras; Danielle Soares deOliveira; Samara Rufino Zampil dosSantos; Luiz Felipe Lobo Ferreira; César Augusto Ferreira Alves Filho; Bruno Alexandre Côrtes; Helenice Charchat‐Fichman (Clinical Case Reports)
ABSTRACT Intracranial Rosai‐Dorfman disease (RDD) is rarely reported in the literature. Up to the present date, there are no documented studies regarding the neuropsychological aspects of a patient with this diagnosis. This study fills this gap, reporting a case of a patient with petroclival RDD, emphasizing the importance of cognitive investigation.